A rapid and reliable technique for N-nitrosodimethylamine analysis in reclaimed water by HPLC-photochemical reaction-chemiluminescence. (October 2016) - Fujioka, Takahiro; Takeuchi, Haruka; Tanaka, Hiroaki; Nghiem, Long D.; Ishida, Kenneth P.; Kodamatani, Hitoshi
Abstract: A fast and reliable analytical technique was evaluated and validated for determination of N -nitrosodimethylamine (NDMA) formation and rejection by reverse osmosis (RO) membranes in potable water reuse applications. The analytical instrument used in this study is high-performance liquid chromatography (HPLC), photochemical reaction (PR) and chemiluminescence (CL) – namely HPLC-PR-CL. Results reported here show that HPLC-PR-CL can be used to measure NDMA with a similar level of accuracy compared to conventional and more time-consuming techniques using gas chromatography and tandem mass spectrometry detection in combination with solid phase extraction. Among key residual chemicals (i.e. monochloramine, hydrogen peroxide and hypochlorite) in reclaimed wastewater, hypochlorite was the only constituent that interfered with the determination of NDMA by HPLC-PR-CL. However, hypochlorite interference was eliminated by adding ascorbic acid as a reducing agent. Direct injection of ultrafiltration (UF)-treated wastewater samples into HPLC-PR-CL also resulted in an underestimation of the NDMA concentration possibly due to interference by organic substances in the UF-treated wastewater. Accurate determination of NDMA concentrations in UF-treated wastewater was achieved by reducing the sample injection volume from 200 to 20 μL, though this increased the method detection limit from 0.2 to 2 ng/L. In contrast, no interference was observed with RO permeate. These results suggest that RO membranes could remove part of substances that interfere with the NDMA analysis by HPLC-PR-CL. In addition, RO treatment experiments demonstrated that HPLC-PR-CL was capable of evaluating near real-time variation in NDMA rejection by RO. Graphical abstract: Highlights: HPLC-PR-CL was evaluated for rapid analysis of NDMA in reclaimed water. No interference of NH2 Cl and H2 O2 on the NDMA analysis was observed. Interference of hypochlorite was eliminated with reducing agent. Reduction in injection volume countered the interference of UF-treated wastewater. HPLC-PR-CL allowed for fast evaluation of NDMA formation and rejection by RO.